Analisis Faktor Yang Berhubungan Dengan Pemanfaatan Jaminan Persalinan Di Wilayah Kerja Puskesmas Tanjung Puri Kabupaten Sintang Tahun 2013 - - Rudiansyah; Chriswardani Suryawati; Ayun Sriatmi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Jampersal is afinancial guarantees delivery services hat include prenatal care, delivery assistance, postpartum care including family planning services, postpartum and newborn careby health workersat health facilities. Jampersal maternity coverage in PHC Tanjung Puri in 2011 accounted for 36% and 24% coverage in 2012. The purpose of this study to determine Knowing the factors related to the utilization Jampersalin Puskesmas PuriTanjung Sintang. This research uses quantitative research withex planatory approach recearch, population in this studyis the total number of women giving birth with 498 people then the samples were taken by 90 respondent sandusing purposive sampling method. Data analysis using Chi Square with assignificance level of 5% or 0,05. Results of this study indicate that as many as four factors related and 2 unrelated factors. Obtained from statistical test p-value = needs (0,037), affordability (0,172), availability (0,871), socialization (0,0029), knowledge (0,005), attitude (0.007), age (0,422), education (1,000), job (1,000), income (0,902). This study suggests that factors related to the utilization of Jampersal are needed, socialization, knowledge and attitudes, while factors that are not related to the utilization of Jampersal is affordability and availability. Puskesmas Puri Tanjung suggestions to improve the performance of health services, especially service delivery and Sintang DHO advised to make out reach programs to the community through counseling and seminars or by distribution of leaflets about the labor insurance program